Whole exome sequencing in a large pedigree with DCM identifies a novel mutation in . - Robyns, Tomas; Willems, Rik; Van Cleemput, Johan; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Breckpot, Jeroen; Devriendt, Koenraad; Corveleyn, Anniek (Acta Cardiol, 2020)
Familial dilated cardiomyopathy (DCM) is genetically heterogeneous and is associated with mutations in at least 40 different genes. Apart from encoding the giant protein Titin, none of these genes have an expected diagnostic yield of more than 5% complicating genetic diagnosis. Whole exome sequencing (WES) is a powerful alternative for the identification of the causal gene, however variant interpretation remains challenging. We report on WES in a large family with autosomal dominant DCM complicated by end stage heart failure and non-sustained ventricular arrhythmias in whom no causative mutation was identified using a targeted gene panel including 28 genes. WES was applied on 2 affected cousins. Stringent filtering of the identified genetic variants was performed including population variant frequencies, in silico analysis, orthologous and paralogous conservation. Subsequently Sanger sequencing was performed for 10 potential disease causing variants in order to confirm the presence of the variant and to evaluate co-segregation. Only one variant in exon 9 of the RBM20 gene (c.2714T > A, p.Met950Lys, NM_001334363) showed full co-segregation in the 7 affected family members resulting in a maximum 2-point LOD score of 2.1 and suggesting this as the pathogenic mutation responsible for the phenotype. Recently mutations in RBM20 have been linked to arrhythmogenic dilated cardiomyopathy caused by defective splicing of the giant sarcomere protein titin and abnormal calcium handling. We report the identification of a novel mutation in RBM20 by WES in a large pedigree with DCM.

A comprehensive clinical and genetic study in 127 patients with ID in Kinshasa, DR Congo. - Lumaka, Aimé; Race, Valerie; Peeters, Hilde; Corveleyn, Anniek; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Song, Xiaofei; Mubungu, Gerrye; Posey, Jennifer; Lupski, James R; Vermeesch, Joris R; Lukusa, Prosper; et al. (Am J Med Genet A, 2018)
Pathogenic variants account for 4 to 41% of patients with intellectual disability (ID) or developmental delay (DD). In Sub-Saharan Africa, the prevalence of ID is thought to be higher, but data in Central Africa are limited to some case reports. In addition, clinical descriptions of some syndromes are not available for this population. This study aimed at providing an estimate for the fraction of ID/DD for which an underlying etiological genetic cause may be elucidated and provide insights into their clinical presentation in special institutions in a Central African country. A total of 127 patients (33 females and 94 males, mean age 10.03 ± 4.68 years), were recruited from six institutions across Kinshasa. A clinical diagnosis was achieved in 44 but molecular confirmation was achieved in 21 of the 22 patients with expected genetic defect (95% clinical sensitivity). Identified diseases included Down syndrome (15%), submicroscopic copy number variants (9%), aminoacylase deficiency (0.8%), Partington syndrome in one patient (0.8%) and his similarly affected brother, X-linked syndromic Mental Retardation type 33 (0.8%), and two conditions without clear underlying molecular genetic etiologies (Oculo-Auriculo-Vertebral and Amniotic Bands Sequence). We have shown that genetic etiologies, similar to those reported in Caucasian subjects, are a common etiologic cause of ID in African patients from Africa. We have confirmed the diagnostic utility of clinical characterization prior to genetic testing. Finally, our clinical descriptions provide insights into the presentation of these genetic diseases in African patients.